Polyethylene polyamine salt interface passivation layer and perovskite solar cell
By using a polyethylene polyamine salt interface passivation layer, the problems of weak binding ability of organic ammonium salt passivation molecules and the impact of accumulation on charge transport in perovskite solar cells were solved, achieving more efficient charge transport and improved cell performance.
Patent Information
- Application Number
- CN202511083038.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-04
- Publication Date
- 2025-11-07
AI Technical Summary
In existing perovskite solar cells, the commonly used organic ammonium salt passivation molecules have a weak binding ability with the perovskite surface and tend to stack vertically to form a transport barrier, which affects the charge extraction efficiency.
Polyethylene polyamine salt is used as the interface passivation layer to provide more passivation sites, and it is distributed in a flat pattern on the perovskite surface to avoid vertical accumulation and improve charge transport effect.
It enhances the bonding ability between the passivation layer and the perovskite surface, reduces the transport barrier, and improves the open-circuit voltage, short-circuit current density, fill factor, and photoelectric conversion efficiency of the battery.
Smart Images

Figure CN120916574A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the field of photovoltaics, and particularly relates to a multi-ethylene polyamine salt interface passivation layer and a perovskite solar cell. BACKGROUND
[0002] At present, perovskite solar cells are recognized as the most promising third-generation photovoltaic technology, and their photoelectric conversion efficiency has been continuously rising from ~10% to >26%, but there is still a gap from the theoretical limit. Therefore, how to improve the efficiency of perovskite solar cells is the focus of attention of the industry and academia.
[0003] In view of the characteristics that the interface structure of the perovskite light-absorbing layer is prone to dissociation and defects, molecular passivation on the surface of the perovskite is an important means to prevent defects and improve device performance.
[0004] Current solutions mainly include introducing organic ammonium salts for surface passivation, such as using propylamine hydroiodide (PAI), ethane-1, 2-diammonium iodide (EDAI2), and propane-1, 3-diammonium iodide (PDAI2) to modify the perovskite / electron transport layer (ETL) interface. However, the organic amine functional group in the above commonly used organic ammonium salt passivation molecules is located at the end of the molecule (one end or both ends). This molecular structure brings two problems: the molecule can usually only bind to a single active site on the surface of the perovskite, and the binding ability is weak; unit point passivation molecules tend to be vertically and closely packed on the surface of the perovskite, which may introduce a transport barrier at the perovskite / electron transport layer interface, affecting charge extraction.
[0005] Therefore, it is urgent to seek a passivation material that can bind to multiple sites at the perovskite / electron transport layer interface and improve the transport effect. SUMMARY
[0006] The present application proposes a multi-ethylene polyamine salt interface passivation layer and a perovskite solar cell to solve the above problems in the prior art. Compared with conventional end organic amine passivation materials, the multi-ethylene polyamine salt interface passivation layer of the present application provides more passivation sites, and the multi-ethylene polyamine salt is distributed in a flat manner at the perovskite / electron transport layer interface, which does not cause the passivation molecules to be vertically stacked and block electron transport, thereby improving charge transport and enhancing cell performance.
[0007] Specifically, one aspect of the present application provides an interface passivation layer, the interface passivation layer comprising a multi-ethylene polyamine salt, the multi-ethylene polyamine salt comprising one or more multi-ethylene polyamines of the chemical formula H2N(CH2CH2NH) n H, n being an integer selected from 2 to 5, the multi-ethylene polyamine salt comprising one or more anions selected from halide ions, carboxylate ions, phosphonate ions, and sulfonate ions.
[0008] In one or more embodiments, the interface passivation layer has a thickness of 0.2-5 nm, preferably 0.5-3 nm.
[0009] In one or more embodiments, the halide ion is selected from one or more of fluoride ion, chloride ion, bromide ion, and iodide ion.
[0010] In one or more embodiments, the carboxylate ion is R1-COO - , R1 being selected from the group consisting of C1-C10 alkyl, C6-C12 substituted C1-C10 alkyl, C6-C12 aryl, and C1-C10 alkyl substituted C6-C12 aryl.
[0011] In one or more embodiments, the carboxylate ion is acetate ion.
[0012] In one or more embodiments, the sulfonate ion is R2-SO3 - , R2 being selected from the group consisting of C1-C10 alkyl, C6-C12 substituted C1-C10 alkyl, C6-C12 aryl, and C1-C10 alkyl substituted C6-C12 aryl.
[0013] In one or more embodiments, the sulfonate ion is p-toluene sulfonate ion.
[0014] In one or more embodiments, the phosphonate ion is selected from R3, R4, and R5 are each independently selected from the group consisting of C1-C10 alkyl, C6-C12 substituted C1-C10 alkyl, C6-C12 aryl, and C1-C10 alkyl substituted C6-C12 aryl.
[0015] In one or more embodiments, the molar ratio of anion to N atom in the polyethylene polyamine salt is < 1 : 1, preferably 1 : 1.
[0016] In one or more embodiments, the anion is selected from one or more of chloride ion, iodide ion, and sulfonate ion.
[0017] In one or more embodiments, the polyethylene polyamine is selected from one or more of triethylene tetramine, tetraethylene pentamine, and pentaethylene hexamine.
[0018] In one or more embodiments, the polyethylene polyamine salt is selected from one or more of triethylene tetramine hydrochloride, tetraethylene pentamine iodide, and pentaethylene hexamine sulfonate.
[0019] In one or more embodiments, the polyethylene polyamine salt is selected from one or more of triethylene tetramine tetrahydrochloride, tetraethylene pentamine pentaiodide, and pentaethylene hexamine hexasulfonate.
[0020] Another aspect of the present application provides a method for preparing the interfacial passivation layer described in the present application, the method comprising preparing the interfacial passivation layer by using a coating method or an evaporation plating method, the coating method comprising one or both of spin coating and slot coating.
[0021] In one or more embodiments, the interfacial passivation layer is prepared by using a coating method, and a polyvinyl polyamine salt is dissolved in a solution to obtain a coating solution.
[0022] In one or more embodiments, the solvent is selected from one or more of isopropyl alcohol, chlorobenzene, toluene, anisole, trifluoroethanol, and ethyl acetate.
[0023] In one or more embodiments, the concentration of the polyvinyl polyamine salt in the coating solution is 0.1-2 mg / mL, preferably 0.5±0.1 mg / mL.
[0024] The present application provides a perovskite solar cell comprising the interfacial passivation layer described in the present application.
[0025] In one or more embodiments, the perovskite solar cell comprises an electron transport layer and a perovskite layer, and the interfacial passivation layer is located between the electron transport layer and the perovskite layer.
[0026] In one or more embodiments, the perovskite layer of the perovskite solar cell comprises a compound ABX3, wherein the A ion is a monovalent cation selected from one or more of Cs + , Rb + , methylamine ion, and formamidinium ion; the B ion is a divalent cation selected from one or more of Pb 2+ , Cu 2+ , Zn 2+ , Ga 2+ , Sn 2+ , and Ca 2+ ; and the X ion is a monovalent anion selected from one or more of I - , Br - , Cl - , F - , and SCN - .
[0027] In one or more embodiments, the perovskite solar cell is prepared from a perovskite precursor solution, and the concentration of the perovskite precursor solution is 0.8-1.6 mol / mL, preferably 1.2±0.1 mol / mL.
[0028] In one or more embodiments, the thickness of the perovskite layer is 100 nm-5 μm.
[0029] The present application provides use of the interfacial passivation layer described in the present application in a solar cell, or use in improving the open-circuit voltage, short-circuit current density, fill factor and / or photoelectric conversion efficiency of a perovskite solar cell. BRIEF DESCRIPTION OF DRAWINGS
[0030] Figure 1 A perovskite solar cell structure in some embodiments of the present application. DETAILED DESCRIPTION
[0031] To enable persons skilled in the art to understand the features and effects of the present application, the following is a general description and definition of the terms and phrases mentioned in this document. Unless otherwise specified, all technical and scientific words used in this document have their usual meanings understood by those skilled in the art of the present application, and in the event of a conflict, the definitions in this specification shall prevail.
[0032] Theories or mechanisms described and disclosed herein, whether correct or not, should not be considered limiting on the scope of the present application, i.e., the present application can be practiced without regard to any particular theory or mechanism.
[0033] In this document, "comprise", "include", "contain", and similar words cover the meanings of "consist essentially of" and "consist of", e.g., when this document discloses that "A comprises B and C", "A consists essentially of B and C" and "A consists of B and C" should be considered to have been disclosed herein.
[0034] In this document, all features defined in the form of numerical ranges or percentage ranges, such as values, amounts, contents and concentrations, are for the sake of brevity and convenience. Accordingly, the description of numerical ranges or percentage ranges should be considered to have encompassed and specifically disclosed all possible sub-ranges and individual values within the range (including integers and fractions).
[0035] In this document, unless otherwise specified, percentages refer to mass percentages, and ratios refer to mass ratios.
[0036] In this document, the sum of the percentages of the components of a composition is 100%.
[0037] In this document, when describing embodiments or examples, it should be understood that they are not intended to limit the present application to these embodiments or examples. On the contrary, all alternatives, modifications and equivalents of the methods and materials described in the present application are intended to be encompassed within the scope of the present application.
[0038] In the present specification, all possible combinations of the technical features in each embodiment or example are not described in order to make the description simple. Therefore, as long as the combinations of the technical features do not contradict each other, any combination of the technical features in each embodiment or example can be made, and all possible combinations should be considered as the scope of the present specification.
[0039] The present application is to improve the problem of easy dissociation of perovskite light-absorbing layer interface structure, and efficiently passivate defects, and a polyethylene polyamine salt is selected as an organic passivation layer, a polyamine structure is used to make the passivation material and the perovskite surface form multi-site combination, and the polyethylene polyamine salt passivation molecules are distributed on the perovskite surface, so that the transmission barrier caused by vertical accumulation is effectively avoided, and charge extraction is facilitated.
[0040] In the present application, the polyethylene polyamine salt is deposited on the perovskite / electron transport layer interface by spin coating, coating, evaporation plating and the like, so as to play a role in defect passivation.
[0041] The chemical formula of the polyethylene polyamine is H2N(CH2CH2NH) n H, n is 2, 3, 4 or 5. Preferably, n is 3, 4 or 5.
[0042] When n=2, H2N(CH2CH2NH) n H is C4H 13 N3 (i.e. diethylene triamine). When n=3, H2N(CH2CH2NH) n H is C6H 18 N4 (i.e. triethylene tetramine). When n=4, H2N(CH2CH2NH) n H is C8H 23 N5 (i.e. tetraethylene pentamine). When n=5, H2N(CH2CH2NH) n H is C 10 H 28 N6 (i.e. pentaethylene hexamine). It is found that the triethylene tetramine salt, the tetraethylene pentamine salt and the pentaethylene hexamine salt can more efficiently passivate the perovskite interface defects, improve the charge transport and improve the battery performance.
[0043] In the present application, the polyethylene polyamine salt can include one or more polyethylene polyamines, i.e. the polyethylene polyamine salt can be a diethylene triamine salt, a triethylene tetramine salt, a tetraethylene pentamine salt or a pentaethylene hexamine salt, or can be a complex salt containing two or more polyethylene polyamines.
[0044] In the present application, the polyethylene polyamine salt can include one or more anions selected from halide ions, carboxylate ions, phosphonate ions and sulfonate ions, i.e. the polyethylene polyamine salt can be a halide, a carboxylate, a phosphonate or a sulfonate, or can be a mixed salt containing two or more anions.
[0045] In the present application, the halide ion can be selected from one or more of fluoride ion, chloride ion, bromide ion and iodide ion.
[0046] In the present application, the carboxylate ion can be R1-COO - , R1 being selected from the group consisting of C1-C10 alkyl, C6-C12 substituted C1-C10 alkyl, C6-C12 aryl and C1-C10 alkyl substituted C6-C12 aryl. In some embodiments, the carboxylate ion is acetate ion (CH3COO - )
[0047] In the present application, the sulfonate ion can be R2-SO3 - , R2 being selected from the group consisting of C1-C10 alkyl, C6-C12 substituted C1-C10 alkyl, C6-C12 aryl and C1-C10 alkyl substituted C6-C12 aryl. In some embodiments, the sulfonate ion is p-toluene sulfonate ion
[0048]
[0049] In the present application, the phosphonate ion can be selected from R3, R4 and R5 are each independently selected from the group consisting of C1-C10 alkyl, C6-C12 substituted C1-C10 alkyl, C6-C12 aryl and C1-C10 alkyl substituted C6-C12 aryl.
[0050] In the present application, the degree of protonation of the polyethylene polyamine in the polyethylene polyamine salt is not particularly limited and can be partial or complete, i.e. the molar ratio of anion to N atom in the polyethylene polyamine in the monomolecular polyethylene polyamine salt can be < 1 : 1.
[0051] In some preferred embodiments, the polyethylene polyamine in the polyethylene polyamine salt is completely protonated. In this case, the molar ratio of anion to N atom in the polyethylene polyamine in the monomolecular polyethylene polyamine salt can be 1 : 1. For example, the chemical formula of the completely protonated polyethylene polyamine hydrochloride is H2N(CH2CH2NH) n H·(n+1)HCl, n being 2, 3, 4 or 5; the chemical formula of the completely protonated polyethylene polyamine iodide is H2N(CH2CH2NH) n H·(n+1)HI, n being 2, 3, 4 or 5; the chemical formula of the completely protonated polyethylene polyamine bromide is H2N(CH2CH2NH) n H·(n+1)HBr, n being 2, 3, 4 or 5; the chemical formula of the completely protonated polyethylene polyamine carboxylate is H2N(CH2CH2NH) nH-(n+1)R1COOH, n is 2, 3, 4, or 5, and R1 is C1-C10 alkyl, C6-C12 substituted C1-C10 alkyl, C6-C12 aryl, and C1-C10 alkyl substituted C6-C12 aryl; the fully protonated polyethylene polyamine phosphonate has the chemical formula H2N(CH2CH2NH) n H-(n+1) n is 2, 3, 4, or 5, and R4 and R5 are each independently selected from the group consisting of C1-C10 alkyl, C6-C12 substituted C1-C10 alkyl, C6-C12 aryl, and C1-C10 alkyl substituted C6-C12 aryl; the fully protonated polyethylene polyamine sulfonate has the chemical formula H2N(CH2CH2NH) n H-(n+1)R2SO3H, n is 2, 3, 4, or 5, and R3 is C1-C10 alkyl, C6-C12 substituted C1-C10 alkyl, C6-C12 aryl, and C1-C10 alkyl substituted C6-C12 aryl.
[0052] Interface passivation layer and method of making
[0053] The present invention provides an interface passivation layer, the interface passivation layer comprising a polyethylene polyamine salt.
[0054] In the present invention, the polyethylene polyamine is preferably selected from one or more of diethylene triamine, triethylene tetramine, tetraethylene pentamine, and pentaethylene hexamine. In the present invention, the polyethylene polyamine is preferably selected from one or more of triethylene tetramine, tetraethylene pentamine, and pentaethylene hexamine.
[0055] In the present invention, the polyethylene polyamine salt is preferably selected from one or more of polyethylene polyamine hydrochloride, polyethylene polyamine iodide, polyethylene polyamine bromide, polyethylene polyamine carboxylate, polyethylene polyamine phosphonate, and polyethylene polyamine sulfonate. In the present invention, the polyethylene polyamine salt is preferably selected from one or more of polyethylene polyamine hydrochloride, polyethylene polyamine iodide, and polyethylene polyamine sulfonate.
[0056] In some embodiments, the polyethylene polyamine salt is selected from one or more of triethylene tetramine hydrochloride, tetraethylene pentamine iodide, and pentaethylene hexamine sulfonate. In some embodiments, the polyethylene polyamine salt is selected from one or more of triethylene tetramine tetrahydrochloride, tetraethylene pentamine pentaiodide, and pentaethylene hexamine hexasulfonate (e.g., pentaethylene hexamine hexasulfonic acid p-toluenesulfonate).
[0057] In the present application, the thickness of the interface passivation layer is preferably 0.2-5 nm, which can be 0.2 nm, 0.5 nm, 0.6 nm, 0.7 nm, 0.8 nm, 1.0 nm, 1.2 nm, 1.5 nm, 1.7 nm, 1.8 nm, 2.0 nm, 2.5 nm, 3.0 nm, 3.5 nm, 4.0 nm, or 5.0 nm. In some more preferred embodiments, the thickness of the interface passivation layer is 0.5-3 nm. The present application controls the thickness of the interface passivation layer within the above range, which is beneficial to exert the effect of the polyethylene polyamine salt in passivating defects and to make the polyethylene polyamine salt passivation molecules uniformly distributed on the perovskite surface, thereby effectively avoiding the transport barrier caused by vertical accumulation and facilitating charge extraction. In the present application, a too thick interface passivation layer (e.g., greater than 5 nm) is not conducive to charge transport, and a too thin interface passivation layer (e.g., less than 0.2 nm) can result in insufficient coverage of the interface passivation layer on the perovskite layer, which makes the passivation of defects ineffective.
[0058] The present application provides a method for preparing the interface passivation layer of the present application, which comprises preparing the interface passivation layer of the present application by using a coating method or an evaporation plating method. The coating method includes spin coating and slot coating.
[0059] In the present application, the interface passivation layer of the present application is prepared by using a coating method, and the polyethylene polyamine salt is dissolved in a solution to obtain a coating solution.
[0060] In the present application, the solvent is selected from one or more of isopropyl alcohol, chlorobenzene, toluene, anisole, trifluoroethanol, and ethyl acetate.
[0061] In the present application, the concentration of the polyethylene polyamine salt in the coating solution is 0.1-2 mg / mL, preferably 0.5±0.1 mg / mL, such as 0.4 mg / mL, 0.45 mg / mL, 0.5 mg / mL, 0.55 mg / mL, or 0.6 mg / mL.
[0062] Perovskite solar cell
[0063] The present application provides a perovskite solar cell comprising the interface passivation layer of the present application.
[0064] In the present application, the perovskite solar cell comprises an electron transport layer and a perovskite layer. The interface passivation layer of the present application can be located between the electron transport layer and the perovskite layer.
[0065] In this invention, perovskite solar cells include single-junction perovskite solar cells and tandem perovskite solar cells. In this invention, perovskite solar cells include conventional perovskite solar cells and inverted perovskite solar cells. In this invention, perovskite solar cells can include conventional single-junction perovskite solar cells, inverted single-junction perovskite solar cells, conventional tandem perovskite solar cells, and inverted tandem perovskite solar cells.
[0066] In this invention, a formal single-junction perovskite solar cell may sequentially include a transparent conductive substrate, an electron transport layer, an interface passivation layer, a perovskite layer, a hole transport layer, and a back electrode. In some embodiments, the formal single-junction perovskite solar cell further includes a buffer layer located between the transparent conductive substrate and the electron transport layer.
[0067] In this invention, such as Figure 1 As shown, an inverted single-junction perovskite solar cell may sequentially include a transparent conductive substrate, a hole transport layer, a perovskite layer, an interface passivation layer, an electron transport layer, and a back electrode. In some embodiments, the inverted single-junction perovskite solar cell further includes a buffer layer located between the electron transport layer and the back electrode.
[0068] In this invention, the electron transport layer and back electrode of the inverted single-junction perovskite solar cell may also include a hole blocking layer.
[0069] In this invention, the transparent conductive substrate can be selected from one of fluorine-doped tin oxide (FTO) glass, indium tin oxide (ITO) glass, or flexible indium tin oxide (ITO) conductive substrate, with a thickness of 20nm-500nm, such as 20nm, 50nm, 80nm, 100nm, 120nm, 150nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, and 500nm.
[0070] In this invention, the hole transport layer can be selected from one or more of metal oxides, single-molecule self-assembly materials containing phosphate groups, and single-molecule self-assembly materials containing carboxylic acid groups. The single-molecule self-assembly material containing phosphate groups can be selected from one or more of [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid (MeO-2PACz), (2-(9H-carbazole-9-yl)ethyl)phosphonic acid (2PACz), and [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid (Me-4PACz). The metal oxide can be NiO. x .
[0071] In the present application, the thickness of the hole transport layer can be 2-50 nm, such as 2 nm, 5 nm, 10 nm, 12 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm.
[0072] In the present application, the electron transport layer can be selected from one or more of C60 or fullerene derivatives (PCBM), which can be [6,6]-phenyl-C61-butyric acid isomethyl ester (
[60] PCBM) or [6,6]-phenyl-C71-butyric acid isomethyl ester (
[70] PCBM).
[0073] In the present application, the thickness of the electron transport layer can be 5-50 nm, such as 5 nm, 10 nm, 12 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm.
[0074] In the present application, there can be an interface passivation layer of the present application between the electron transport layer and the perovskite layer.
[0075] In the present application, the perovskite layer of the perovskite solar cell has a chemical formula of ABX3, wherein the A ion is a monovalent cation, including but not limited to one of the monovalent cations or a mixture of monovalent cations selected from Cs + , Rb + , methylamine ion and formamidine ion; the B ion is a divalent cation, including but not limited to one of the divalent cations or a mixture of divalent cations selected from Pb 2+ , Cu 2+ , Zn 2+ , Ga 2+ , Sn 2+ and Ca 2+ ; the X ion is a monovalent anion, including but not limited to one of the monovalent anions or a mixture of monovalent anions selected from I - , Br - , Cl - , F - and SCN - .
[0076] In the present application, the concentration of the perovskite precursor solution of the perovskite solar cell can be 0.8-1.6 mol / mL, preferably 1.2±0.1 mol / mL, which can be 0.8 mol / mL, 0.9 mol / mL, 1.0 mol / mL, 1.1 mol / mL, 1.2 mol / mL, 1.3 mol / mL, 0.4 mol / mL, 1.5 mol / mL, 1.6 mol / mL.
[0077] In the present application, the solvent in the perovskite precursor solution is selected from one or more of N,N-dimethylformamide (DMF), dimethyl sulfoxide (DMSO), gamma-butyrolactone (GBL) and N-methyl pyrrolidone (NMF). In some embodiments, the organic solvent is selected from two of N,N-dimethylformamide, dimethyl sulfoxide, gamma-butyrolactone and N-methyl pyrrolidone, and the volume ratio of the two organic solvents is (3-5):1. For example, the organic solvent can be a mixture of N,N-dimethylformamide and dimethyl sulfoxide with a volume ratio of (3-5):1, and the volume ratio can be 3:1, 4:1, 5:1; the organic solvent can also be a mixture of gamma-butyrolactone and N-methyl pyrrolidone with a volume ratio of (3-5):1, and the volume ratio can be 3:1, 4:1, 5:1; the organic solvent can also be a mixture of N,N-dimethylformamide and N-methyl pyrrolidone with a volume ratio of (3-5):1, and the volume ratio can be 3:1, 4:1, 5:1.
[0078] In the present application, the thickness of the perovskite layer can be 10 nm-100 μm, such as 10 nm, 50 nm, 100 nm, 200 nm, 300 nm, 400 nm, 450 nm, 500 nm, 550 nm, 600 nm, 650 nm, 700 nm, 750 nm, 800 nm, 1 μm, 2 μm, 5 μm, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 80 μm, 100 μm.
[0079] In the present application, the method for preparing the perovskite layer includes but is not limited to one or more of spin coating, blade coating, evaporation, printing, spraying, spray pyrolysis, slot coating.
[0080] In the present application, the back electrode can be Ag, Cu or Au.
[0081] In the present application, the thickness of the back electrode can be 60 nm-300 nm, such as 60 nm, 100 nm, 120 nm, 150 nm, 200 nm, 250 nm, 300 nm.
[0082] In the present application, the buffer layer can be selected from one or more of BCP, SnO2, Al2O3 and acetylacetone zirconium.
[0083] In the present application, the thickness of the buffer layer can be 5 nm-50 nm, such as 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm.
[0084] In the present application, the method for preparing the formal single-junction perovskite solar cell can include:
[0085] depositing an electron transport layer on the surface of the transparent conductive substrate;
[0086] depositing an interface passivation layer on the surface of the electron transport layer;
[0087] depositing a perovskite layer on the surface of the interface passivation layer;
[0088] depositing a hole transport layer on the surface of the perovskite layer;
[0089] depositing a back electrode on the surface of the hole transport layer to obtain a formal single-junction perovskite solar cell.
[0090] In some embodiments, the method for preparing a formal single-junction perovskite solar cell further comprises: depositing a buffer layer on the surface of the transparent conductive substrate, and then depositing an electron transport layer on the surface of the buffer layer.
[0091] In the present application, the method for preparing a formal single-junction perovskite solar cell can comprise:
[0092] depositing a hole transport layer on the surface of the transparent conductive substrate;
[0093] depositing a perovskite layer on the surface of the hole transport layer;
[0094] depositing an interface passivation layer on the surface of the perovskite layer;
[0095] depositing an electron transport layer on the surface of the interface passivation layer;
[0096] depositing a back electrode on the surface of the electron transport layer to obtain a formal single-junction perovskite solar cell.
[0097] In some embodiments, the method for preparing a formal single-junction perovskite solar cell further comprises: depositing a buffer layer on the surface of the transparent conductive substrate, and then depositing an electron transport layer on the surface of the buffer layer.
[0098] The present application has the following beneficial effects:
[0099] 1、The polyethylene polyamine salt interface passivation layer of the present application provides more passivation sites, which can effectively prevent defects from being generated, and has good passivation efficiency.
[0100] 2、The polyethylene polyamine salt interface passivation layer of the present application forms a multi-site combination with the perovskite surface, has strong combination ability, and the multi-site combination makes the passivation molecules on the perovskite surface distribute in a tiled manner, reduces the transmission barrier, thereby improving the charge transport efficiency and enhancing the battery performance.
[0101] 3、The polyethylene polyamine salt interface passivation layer of the present application can significantly improve the open-circuit voltage, short-circuit current density, fill factor and photoelectric conversion efficiency of the battery.
[0102] The present invention will be described below by way of specific embodiments. It should be understood that these embodiments are merely illustrative and are not intended to limit the scope of the invention. The methods, reagents, and materials used in the embodiments and comparative examples are conventional methods, reagents, and materials in the art, unless otherwise stated. The starting material compounds in the embodiments and comparative examples are all commercially available.
[0103] Example 1
[0104] (1) A transparent clean glass with a thickness of 3.2 mm was selected, and TCO with a thickness of 100 nm was prepared by magnetron sputtering. The material was ITO.
[0105] (2) HTL with a thickness of 20 nm was prepared by magnetron sputtering. The material was NiO. x ;
[0106] (3) Preparation of perovskite Cs by slit coating 0.05 FA 0.8 MA 0.15 Pb(I 0.75 Br 0.25 )3 serves as the active layer, with a thickness of 500 nm; perovskite (in the form of Pb) in the perovskite precursor solution 2+ The concentration of the perovskite precursor solution was 1.2 mol / mL, and the solvents for the perovskite precursor solution were DMF and DMSO in a volume ratio of 4:1.
[0107] (4) A passivation layer between perovskite and ETL was prepared by thermal evaporation. The material was triethylenetetramine tetrahydrochloride with a thickness of 1 nm.
[0108] (5) ETL was prepared by thermal evaporation with a thickness of 20 nm and the material was C60;
[0109] (6) A buffer layer with a thickness of 20 nm was prepared by atomic layer deposition and the material was SnO2;
[0110] (7) The back electrode was prepared by magnetron sputtering with a thickness of 200 nm and the material was Cu.
[0111] Example 2
[0112] (1) A transparent clean glass with a thickness of 3.2 mm was selected, and TCO with a thickness of 100 nm was prepared by magnetron sputtering. The material was ITO.
[0113] (2) HTL with a thickness of 20 nm was prepared by magnetron sputtering. The material was NiMgLiO. x ;
[0114] (3) Preparation of perovskite Cs by slit coating0.05 FA 0.8 MA 0.15 Pb(I 0.75 Br 0.25 )3as the active layer, with a thickness of 750 nm; the concentration of perovskite (calculated as Pb 2+ ) in the perovskite precursor solution was 1.2 mol / mL, and the solvent of the perovskite precursor solution was DMF and DMSO, with a volume ratio of 4:1;
[0115] (4) A passivation layer between the perovskite and the ETL was prepared by a slot coating method, with a material of tetraethylenepentamine iodide and a thickness of 1 nm, wherein the solution used was an isopropanol solution of 0.5 mg / mL tetraethylenepentamine pentaiodide;
[0116] (5) The ETL was prepared by thermal evaporation, with a thickness of 20 nm and a material of C60;
[0117] (6) The buffer layer was prepared by atomic layer deposition, with a thickness of 20 nm and a material of SnO2;
[0118] (7) The back electrode was prepared by magnetron sputtering, with a thickness of 200 nm and a material of Cu.
[0119] Example 3
[0120] (1) A transparent clean glass with a thickness of 3.2 mm was selected, and a TCO was prepared by magnetron sputtering, with a thickness of 100 nm and a material of ITO;
[0121] (2) The HTL was prepared by magnetron sputtering, with a thickness of 20 nm and a material of NiMgLiO x ;
[0122] (3) Perovskite Cs 0.05 FA 0.8 MA 0.15 Pb(I 0.75 Br 0.25 )3was prepared as the active layer by slot coating, with a thickness of 750 nm; the concentration of perovskite (calculated as Pb 2+ ) in the perovskite precursor solution was 1.2 mol / mL, and the solvent of the perovskite precursor solution was DMF and DMSO, with a volume ratio of 4:1;
[0123] (4) A passivation layer between the perovskite and the ETL was prepared by thermal evaporation, with a material of pentaethylenehexamine hexa-p-toluenesulfonate and a thickness of 1 nm;
[0124] (5) The ETL was prepared by thermal evaporation, with a thickness of 20 nm and a material of C60;
[0125] (6) The buffer layer is prepared by atomic layer deposition method, with a thickness of 20 nm and a material of SnO2;
[0126] (7) The back electrode is prepared by magnetron sputtering method, with a thickness of 200 nm and a material of Cu.
[0127] Example 4
[0128] (1) The transparent clean glass with a thickness of 3.2 mm is selected, and the TCO is prepared by magnetron sputtering, with a thickness of 100 nm and a material of ITO;
[0129] (2) The HTL is prepared by magnetron sputtering method, with a thickness of 20 nm and a material of NiMgLiO x ;
[0130] (3) The perovskite Cs 0.05 FA 0.8 MA 0.15 Pb(I 0.75 Br 0.25 )3 is prepared as the active layer by slot coating, with a thickness of 750 nm; the concentration of perovskite (calculated based on Pb 2+ ) in the perovskite precursor solution is 1.2 mol / mL, and the solvent of the perovskite precursor solution is DMF and DMSO, with a volume ratio of 4:1;
[0131] (4) The passivation layer between the perovskite and the ETL is prepared by thermal evaporation, with a material of pentaethylene hexamine hexa-p-toluenesulfonate and a thickness of 0.5 nm;
[0132] (5) The ETL is prepared by thermal evaporation, with a thickness of 20 nm and a material of C60;
[0133] (6) The buffer layer is prepared by atomic layer deposition method, with a thickness of 20 nm and a material of SnO2;
[0134] (7) The back electrode is prepared by magnetron sputtering method, with a thickness of 200 nm and a material of Cu.
[0135] Example 5
[0136] (1) The transparent clean glass with a thickness of 3.2 mm is selected, and the TCO is prepared by magnetron sputtering, with a thickness of 100 nm and a material of ITO;
[0137] (2) The HTL is prepared by magnetron sputtering method, with a thickness of 20 nm and a material of NiMgLiO x ;
[0138] (3) The perovskite Cs 0.05 FA 0.8 MA 0.15 Pb(I0.75 Br 0.25 )3 as the active layer, thickness of 750 nm; concentration of perovskite (calculated as Pb 2+ ) in perovskite precursor solution is 1.2 mol / mL, solvent of perovskite precursor solution is DMF and DMSO, volume ratio of which is 4:1;
[0139] (4) a passivation layer between perovskite and ETL is prepared by thermal evaporation, material is pentaethylene hexamine hexa-p-toluenesulfonate, thickness of which is 3 nm;
[0140] (5) ETL is prepared by thermal evaporation, thickness of which is 20 nm, material is C60;
[0141] (6) a buffer layer is prepared by atomic layer deposition, thickness of which is 20 nm, material is SnO2;
[0142] (7) a back electrode is prepared by magnetron sputtering, thickness of which is 200 nm, material is Cu.
[0143] Example 6
[0144] (1) transparent clean glass with thickness of 3.2 mm is selected, TCO is prepared by magnetron sputtering, thickness of which is 100 nm, material is ITO;
[0145] (2) HTL is prepared by magnetron sputtering, thickness of which is 20 nm, material is NiMgLiO x ;
[0146] (3) perovskite Cs 0.05 FA 0.8 MA 0.15 Pb(I 0.75 Br 0.25 )3 is prepared by slot coating as the active layer, thickness of which is 750 nm; concentration of perovskite (calculated as Pb 2+ ) in perovskite precursor solution is 1.2 mol / mL, solvent of perovskite precursor solution is DMF and DMSO, volume ratio of which is 4:1;
[0147] (4) a passivation layer between perovskite and ETL is prepared by thermal evaporation, material is pentaethylene hexamine hexa-p-toluenesulfonate, thickness of which is 0.2 nm;
[0148] (5) ETL is prepared by thermal evaporation, thickness of which is 20 nm, material is C60;
[0149] (6) a buffer layer is prepared by atomic layer deposition, thickness of which is 20 nm, material is SnO2;
[0150] (7) a back electrode is prepared by magnetron sputtering, thickness of which is 200 nm, material is Cu.
[0151] Example 7
[0152] (1) A transparent clean glass with a thickness of 3.2 mm was selected, and a TCO was prepared by magnetron sputtering, with a thickness of 100 nm and a material of ITO;
[0153] (2) An HTL was prepared by magnetron sputtering, with a thickness of 20 nm and a material of NiMgLiO x ;
[0154] (3) A perovskite Cs 0.05 FA 0.8 MA 0.15 Pb(I 0.75 Br 0.25 )3 was prepared as an active layer by slot coating, with a thickness of 750 nm; the concentration of the perovskite (calculated as Pb 2+ ) in the perovskite precursor solution was 1.2 mol / mL, and the solvent of the perovskite precursor solution was DMF and DMSO, with a volume ratio of 4:1;
[0155] (4) A passivation layer between the perovskite and the ETL was prepared by thermal evaporation, with a material of pentaethylene hexamine hexa-p-toluenesulfonate and a thickness of 5 nm;
[0156] (5) An ETL was prepared by thermal evaporation, with a thickness of 20 nm and a material of C60;
[0157] (6) A buffer layer was prepared by atomic layer deposition, with a thickness of 20 nm and a material of SnO2;
[0158] (7) A back electrode was prepared by magnetron sputtering, with a thickness of 200 nm and a material of Cu.
[0159] Comparative Example 1
[0160] (1) A transparent clean glass with a thickness of 3.2 mm was selected, and a TCO was prepared by magnetron sputtering, with a thickness of 100 nm and a material of ITO;
[0161] (2) An HTL was prepared by magnetron sputtering, with a thickness of 20 nm and a material of NiMgLiO x ;
[0162] (3) A perovskite Cs 0.05 FA 0.8 MA 0.15 Pb(I 0.75 Br 0.25 )3 was prepared as an active layer by slot coating, with a thickness of 750 nm; the concentration of the perovskite (calculated as Pb 2+The concentration of the perovskite precursor solution was 1.2 mol / mL, and the solvents for the solution were DMF and DMSO in a volume ratio of 4:1.
[0163] (4) A passivation layer between perovskite and ETL was prepared by thermal evaporation. The material was pentaethylenehexamine and the thickness was 1 nm.
[0164] (5) ETL was prepared by thermal evaporation with a thickness of 20 nm and the material was C60;
[0165] (6) A buffer layer with a thickness of 20 nm was prepared by atomic layer deposition and the material was SnO2.
[0166] (7) The back electrode was prepared by magnetron sputtering with a thickness of 200 nm and the material was Cu.
[0167] Comparative Example 2
[0168] (1) A transparent clean glass with a thickness of 3.2 mm was selected, and TCO with a thickness of 100 nm was prepared by magnetron sputtering. The material was ITO.
[0169] (2) HTL with a thickness of 20 nm was prepared by magnetron sputtering. The material was NiMgLiO. x ;
[0170] (3) Preparation of perovskite Cs by slit coating 0.05 FA 0.8 MA 0.15 Pb(I 0.75 Br 0.25 )3 serves as the active layer, with a thickness of 750 nm. Tetraethylenepentamine pentaiodide at a concentration of 0.3 mg / mL is added to the perovskite precursor solution. The perovskite in the perovskite precursor solution (in Pb...) 2+ The concentration of the perovskite precursor solution was 1.2 mol / mL, and the solvents for the solution were DMF and DMSO in a volume ratio of 4:1.
[0171] (4) A LiF passivation layer with a thickness of 1.5 nm was prepared by thermal evaporation;
[0172] (5) ETL was prepared by thermal evaporation with a thickness of 20 nm and the material was C60;
[0173] (6) A buffer layer with a thickness of 20 nm was prepared by atomic layer deposition and the material was SnO2.
[0174] (7) The back electrode was prepared by magnetron sputtering with a thickness of 200 nm and the material was Cu.
[0175] Blank example
[0176] (1) The transparent clean glass with a thickness of 3.2 mm was selected, and TCO was prepared by magnetron sputtering, with a thickness of 100 nm and ITO as the material;
[0177] (2) HTL was prepared by magnetron sputtering method, with a thickness of 20 nm and NiMgLiO as the material x ;
[0178] (3) Perovskite Cs 0.05 FA 0.8 MA 0.15 Pb(I 0.75 Br 0.25 )3 was prepared as an active layer by slot coating, with a thickness of 750 nm; the concentration of perovskite (calculated based on Pb 2+ ) in the perovskite precursor solution was 1.2 mol / mL, and the solvent of the perovskite precursor solution was DMF and DMSO, with a volume ratio of 4:1;
[0179] (4) LiF passivation layer was prepared by thermal evaporation, with a thickness of 1.5 nm;
[0180] (5) ETL was prepared by thermal evaporation, with a thickness of 20 nm and C60 as the material;
[0181] (6) The buffer layer was prepared by atomic layer deposition method, with a thickness of 20 nm and SnO2 as the material;
[0182] (7) Back electrode was prepared by magnetron sputtering method, with a thickness of 200 nm and Cu as the material.
[0183] Test Example
[0184] Performance test of perovskite solar device: the current output of perovskite solar cells prepared in Examples 1-7, Comparative Examples 1-2 and Blank Example at different voltages was tested at 25°C using a solar simulator (AM 1.5G standard solar spectrum, incident light power P in is 100 mW / cm 2 ), and the voltage range was set to 15V to-0.5V. The effective area of the cell was 36 cm 2 , and 10 sub-cells were connected in series. The open-circuit voltage, short-circuit current density, fill factor and photoelectric conversion efficiency of the perovskite solar cells prepared in Examples 1-7, Comparative Examples 1-2 and Blank Example were obtained according to the characteristic curve.
[0185] (1) Open-circuit voltage (V oc ): the voltage value corresponding to the current equal to zero.
[0186] (2) Short-circuit current density (J sc ): the current size (Jsc )..
[0187] (3) Fill factor (FF): the ratio of the maximum output power (P max ) of the battery to the product of the open-circuit voltage and the short-circuit current, the calculation formula is (P max / V oc *I sc )*100%, wherein the maximum power point is the point at which the battery output power reaches the maximum value, and I sc is the short-circuit current.
[0188] (4) Photoelectric conversion efficiency (PCE): the photoelectric conversion efficiency refers to the ratio of the maximum output power to the incident light power (P in ), the calculation formula is (P max / P in )*100%.
[0189] The performance test results of the perovskite solar cells prepared in Examples 1-7, Comparative Examples 1-2 and the blank example are shown in Table 1.
[0190] Table 1
[0191]
[0192] By comparing the performance test results of Examples 1-7 and the blank example, it can be seen that after replacing the passivation layer between the perovskite layer and the electron transport layer from LiF (blank example) to polyethylene polyamine salt (Examples 1-5), the open-circuit voltage, short-circuit current density, fill factor and photoelectric conversion efficiency of the battery are all significantly improved.
[0193] The difference between Example 3 and Comparative Example 1 is that Example 3 uses salted pentaethylene hexamine sulfonate as the passivation layer, while Comparative Example 1 uses unsalted pentaethylene hexamine as the passivation layer. By comparing the performance test results of Example 3, Comparative Example 1 and the blank example, it can be seen that compared with LiF, unsalted polyethylene polyamine as a passivation layer has a slight effect on improving the open-circuit voltage and photoelectric conversion efficiency, but has no effect on improving the short-circuit current density, and has an adverse effect on the fill factor; while polyethylene polyamine salt as a passivation layer has a significant effect on improving the open-circuit voltage, short-circuit current density, fill factor and photoelectric conversion efficiency.
[0194] The different effects of the polyethylene polyamine salt and the polyethylene polyamine on the passivation of the perovskite interface are mainly because: compared with the pure polyethylene polyamine, the salted polyethylene polyamine molecule contains halogen ions, carboxylate ions, phosphonate ions, sulfonate ions and other anions in addition to amino groups. The amino group can directly form a coordination bond with the uncoordinated lead ion on the surface of the perovskite, filling the metal vacancy defects. The anion can ionically compensate for the iodine vacancies and other defects on the interface of the perovskite, and can also form a coordination bond with the uncoordinated lead ion. The amino group and the anion can play a synergistic role in the passivation process on the interface of the perovskite.
[0195] The difference between Example 2 and Comparative Example 2 is that Example 2 uses tetraethylenepentamine iodide as the passivation layer, while Comparative Example 2 uses LiF as the passivation layer and additionally dopes tetraethylenepentamine iodide in the perovskite layer. By comparing the performance test results of Example 3, Comparative Example 1 and the blank example, it can be seen that doping polyethylene polyamine salt in the perovskite layer only has a slight effect on the open-circuit voltage, fill factor and photoelectric conversion efficiency; while the polyethylene polyamine salt as the passivation layer has a significant effect on the open-circuit voltage, short-circuit current density, fill factor and photoelectric conversion efficiency.
Claims
1. An interfacial passivation layer, characterized in that, The interface passivation layer comprises a polyethylene polyamine salt comprising one or more polyethylene polyamines of the formula H2N(CH2CH2NH) n H, n is an integer selected from 2 to 5, the polyethylene polyamine salt comprising one or more anions selected from halide ions, carboxylate ions, phosphonate ions, and sulfonate ions.
2. The interface passivation layer of claim 1, wherein, The interface passivation layer has a thickness of 0.2-5 nm, preferably 0.5-3 nm.
3. The interface passivation layer of claim 1, wherein, The halide ion is selected from one or more of fluoride ion, chloride ion, bromide ion and iodide ion.
4. The interface passivation layer of claim 1, wherein, said carboxylate ion is R1-COO - R1 is selected from the group consisting of C1-C10 alkyl, C6-C12 substituted C1-C10 alkyl, C6-C12 aryl and C1-C10 alkyl substituted C6-C12 aryl; preferably, said carboxylate ion is an acetate ion.
5. The interface passivation layer of claim 1, wherein, said sulfonate ion is R2-SO3 - R2 is selected from the group consisting of C1-C10 alkyl, C6-C12 substituted C1-C10 alkyl, C6-C12 aryl and C1-C10 alkyl substituted C6-C12 aryl; preferably, said sulfonate ion is p-toluenesulfonate ion.
6. The interface passivation layer of claim 1, wherein, said phosphonate ion is selected from the group consisting of R3, R4and R5are each independently selected from the group consisting of C1-C10alkyl, C6-C12substituted C1-C10alkyl, C6-C12aryl and C1-C10alkyl substituted C6-C12aryl.
7. The interface passivation layer of claim 1, wherein, The molar ratio of anion to N atom in the polyethylene polyamine is ≤1:1, preferably 1:
1.
8. The interface passivation layer of claim 1, wherein, The anion is selected from one or more of chloride ion, iodide ion and sulfonate ion.
9. The interface passivation layer of claim 1, wherein, The polyethylene polyamine is selected from one or more of triethylenetetramine, tetraethylenepentamine and pentaethylenehexamine.
10. The interface passivation layer of claim 1, wherein, The polyethylene polyamine salt is selected from one or more of triethylenetetramine hydrochloride, tetraethylenepentamine iodide and pentaethylenehexamine sulfonate; more preferably, the polyethylene polyamine salt is selected from one or more of triethylenetetramine tetrahydrochloride, tetraethylenepentamine pentaiodide and pentaethylenehexamine hexasulfonate.
11. A method of producing the interfacial passivation layer according to any one of claims 1 to 10, characterized in that, The method comprises preparing the interface passivation layer using a coating method or an evaporation plating method, the coating method comprising one or both of spin coating and slot coating.
12. The method of claim 11, wherein, The interface passivation layer is prepared using a coating method, the polyethylene polyamine salt is dissolved in a solution to obtain a coating solution; the solvent is selected from one or more of isopropyl alcohol, chlorobenzene, toluene, anisole, trifluoroethanol and ethyl acetate; the concentration of the polyethylene polyamine salt in the coating solution is 0.1-2 mg / mL, preferably 0.5±0.1 mg / mL.
13. A perovskite solar cell comprising the interface passivation layer of any one of claims 1-10.
14. The perovskite solar cell of claim 13, wherein the perovskite layer is formed by a two-step method. The perovskite solar cell comprises an electron transport layer and a perovskite layer, and the interface passivation layer is located between the electron transport layer and the perovskite layer.
15. Use of the interface passivation layer of any one of claims 1-10 in a perovskite solar cell, or use in improving the open-circuit voltage, short-circuit current density, fill factor and / or photoelectric conversion efficiency of a perovskite solar cell.